Ultrasensitive, Specific, and Rapid Detection of Mycoplasma pneumoniae Using the ERA/CRISPR–Cas12a Dual System - Deng, Zhongliang; Hu, Haiyang; Tang, Dan; Liang, Jiaxin; Su, Xiaoling; Jiang, Tingqing; Hu, Xipan; Ying, Wanqin; Zhen, Deshuai; Xiao, Xilin; He, Jun (Frontiers in Microbiology, 2022)
Mycoplasma pneumoniae can cause severe respiratory tract infections and extrapulmonary diseases, which pose a significant threat to the health of children. Diagnostic methods for M. pneumoniae include isolation and culture, antibody detection, fluorescence quantitative PCR, and so on, but there are various shortcomings in time, cost, convenience, and sensitivity. In this study, we developed a rapid, sensitive, specific, and economical method for the detection of M. pneumoniae, termed the ERA/CRISPR–Cas12a dual system. The system used the high specificity and collateral cleavage activity of the LbCas12a protein, combined with enzymatic recombination amplification (ERA) technology with strong amplification ability, allowing the results to be observed by a portable fluorometer or visualized by the naked eye with a dipstick, which could be obtained in approximately 30 min. The ERA/CRISPR–Cas12a fluorescence and dipstick system were able to detect M. pneumoniae at titers as low as 1 and 100 copies/μL, respectively. The specificity of the two interpretation methods was 100%, and no cross-reaction with other pathogens was observed. In the evaluation of 92 clinical samples, the positive predictive agreements of the ERA/CRISPR–Cas12a fluorescence and dipstick systems with qPCR detection were 100% and 92.86%, respectively. The negative predictive agreements of both methods were 100%. In conclusion, this study established a portable, rapid, low-cost, ultrasensitive, and specific method for the early and rapid diagnosis of M. pneumoniae to meet the needs of on-site rapid detection in primary health institutions.